Complete Genome Sequence of a Colombian Zika Virus Strain Obtained from BALB/c Mouse Brain after Intraperitoneal Inoculation. (2023)
A Zika virus (ZIKV) strain was isolated from an acute febrile patient during the Zika epidemics in Colombia. The strain was intraperitoneally inoculated into BALB/c mice, and 7 days postinoculation, neurological manifestations and ZIKV infection in the brain were demonstrated. The reported genome sequence is highly related to strains circulating in the Americas.